#AskGaryVee : one entrepreneur's take on leadership, social media, & self-awareness - Vaynerchuk, Gary (Harper Business, an imprint of HarperCollinsPublishers, 2016)
An inspiring entrepreneur, known for his popular The #AskGaryVee Show, highlights the most interesting questions ever posed to him and offers insights and advice on marketing, using social media, creating a personal brand and how to hire superstar employees. --Publisher's description.